A structured graduated protocol with heat denatured eggs in the treatment of egg allergy. Issue 8 (15th November 2019) - Gotesdyner, Leora; Zeldin, Yuri; Machnes Maayan, Diti; Efron, Adi; Stauber, Tali; Maoz Segal, Ramit; Binson, Inga; Dinkin, Mira; Dinkowitz, Larisa; Nevet, Ayelet; Asher, Ilan; Yakar, Yael; et al.
Abstract: Background: Most children with egg allergy (EA) can tolerate extensively heated and baked egg (EHBE). Consumption of EHBE may promote faster resolution of EA; however, no consensus exists as to the required amounts and treatment protocols. Objective: To evaluate the efficacy and safety of a structured graduated exposure protocol (SGEP) with EHBE in promoting tolerance to eggs in EA children under 2 years of age. Methods: In a case‐control study, EA children aged < 2 years who were treated with SGEP including EHBE were compared to children treated with strict avoidance. Data were collected from records and telephone questionnaires. Analysis was performed using non‐parametric Kaplan‐Meier and Cox proportional hazard regression models. Results: Thirty‐nine egg‐allergic children with a median age at intervention of 16 months (interquartile range: 13‐19) were treated with SGEP and followed to a median age of 39 months (26.8‐50.0). The median age at resolution of EA was compared to a matched group of 80 children treated with strict avoidance at least until 2 years of age or earlier natural resolution and followed to a median age of 69 months (46‐104). The median estimated age at EA resolution in the SGEP group was 24 months (95% CI, 19.5‐28.5 months), compared to 78 months (95% CI, 53‐102) in the control group, P  < .001. At last follow‐up, 82% of treated children were tolerant to lightly cooked eggs vs 54% of controls, P  = .001. Conclusion: A structured protocol with EHBE appears to promote faster resolution of EA.